Certification of a New Batch of the Industry Reference Standard of Polysaccharide Content in Schigellvac Vaccine - V. A. Volkov; M. V. Abramtseva; T. I. Nemirovskaya; V. P. Kovtun; O. V. Fadeykina; R. A. Volkova (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The article summarises materials on the certification of the industry reference standard of Schigella sonnei polysaccharide dysentery vaccine (commercial name — Schigellvac). The industry reference standard is used to assess the consistency of the vaccine «Specific activity» testing by passive hemagglutination inhibition assay. A certification programme for the industry reference standard was developed. Samples of the candidate vaccine were tested in terms of the following quality characteristics: «Appearance», «Identification», «Extractable Volume». The test results confirmed that the samples comply with the current requirements of the manufacturer’s product specification file for Schigellvac vaccine. It was determined that the certification parameter — the polysaccharide dilution ratio which results in inhibition of passive hemagglutination in a homologous system — has to fall in the range from 1:128 to 1:512. The following set of standard documents accompanying a scientific/technological product was approved for the industry reference standard No. 42-28-386-2017: passport, patient information leaflet, mockup labels for primary and secondary packaging.